(untitled) (Experimental biology, 2022)
The article provides the most up to date information on the distribution of the red-listed species Hepatica falconeri (Thoms.) Steward (Ranunculaceae), and on its ecological and altitudinal preferences within the mountain ranges of southeastern Kazakhstan based on the analysis of literature sources, her- barium specimens, data from the site https://www.plantarium.ru/, as well as our own research. The authors’ data confirm that the studied species is a forest petromesophilic ecological element. As a result of the research, the floristic composition of plant communities with the participation of H. falconeri in the Taldy gorge (northern macroslope of the Kungei Alatau) was established. It is represented by 107 species from 46 families. The most important are 13 families (64.5%): ...